Partisipasi Anggota Pada Kelompok Tani Sarunta Waya Di Desa Paslaten Kecamatan Kauditan Kabupaten Minahasa Utara - Sitohang, Carolina; Baroleh, Jenny; Timban, Jean Fanny Juanita (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
This research aims to describe the participation of members in the Sarunta Waya Farmers Group in Paslaten Village, Kauditan District, North Minahasa Regency. This research was carried out in Paslaten Village, Kauditan District, North Minahasa Regency. This research starts from April to July 2024. The types of data used in this research are primary data and secondary data. Primary data was obtained from direct interviews with the Sarunta Waya Farmers Group using a questionnaire, while secondary data was obtained from the Paslaten Village government. The data analysis method used in this research is descriptive analysis using a Likert scale. The results of this research indicate that the participation of the Sarunta Waya Farmers Group in Paslaten Village, Kauditan District, North Minahasa Regency at the planning stage and at the implementation stage was classified as actively participating, and the evaluation stage was classified as less participating.